The Effectiveness of Leucodepleted (In Line) and Leucodepleted (Bedsite) In Reducing Leukocytes and Their Effect on Hemoglobin (Hb) and Red Blood Cell (RBC) - Maulana Baihakhi; William Leslie; Silvia Fransisca (International Journal of Health and Pharmaceutical (IJHP), 2023)
Blood transfusion currently plays an important medical role in methods of reducing the number of leukocytes in component products, including reducing the number of leukocytes before storage (pre-storage leucodepletion) and reducing the number of leukocytes after storage (post storage leucodepletion). The purpose of this study was to determine whether there was a comparison of hemolysis events and hematocrit quality in leucodepleted (In Line) and leucodepleted (Bedsite) clinical transfusions at the Blood Transfusion Unit at the Indonesian Red Cross in Medan City. This study was an analytic study with a cross-sectional design of 58 people who were divided into two groups, namely the group with leucodepleted in line and the group with leucodepleted bedsite, inclusion and exclusion criteria. The results showed that the incidence of hemolysis after leucodepleted (in line) was 0% and leucodepleted (bedsite) was 0.02%, where the standard percentage of blood hemolysis was <0.8%, the occurrence of hemolysis after the production process of the two products was very small. While the hematocrit before and after leucodepleted decreased by 35.91% in leucodepleted (in line) and 33.33% in leucodepleted (bedsite). Comparison of leucodepleted (In Line) and leucodepleted (Bedsite) hemolysis events was also found. Where the incidence of leucodepleted (in line) hemolysis is not found, so the leucodepleted (in line) blood component has good quality.